Transcriptional regulation of BNIP3 by Sp3 in prostate cancer. Issue 14 (27th May 2015) - Huang, Ying; Shen, Pengfei; Chen, Xueqin; Chen, Zhibin; Zhao, Tao; Chen, Ni; Gong, Jing; Nie, Ling; Xu, Miao; Li, Xinglan; Zeng, Hao; Zhou, Qiao
<x xml:space="preserve">Abstract</x> BACKGROUND The transcription factors Sp3/Sp1 are expressed in a various types of cancers and BNIP3 is overexpressed in prostate cancer. Although it has been demonstrated that BNIP3 is transcriptionally regulated by HIF‐1α and is post‐transcriptionally regulated by miR145, our previous data indicated that there might be some other transcription factors regulating BNIP3 in prostate cancer. This study is conducted to investigate whether BNIP3 expression is directly regulated by Sp3/Sp1 or not. MATERIALS AND METHODS Bioinformatics analysis shows that BNIP3 promoter contains several potential Sp3/Sp1 binding sites. And then it is demonstrated that SP3 could regulate the BNIP3 transcriptionally by binding to the predicted sites by dual reporter gene assays, ChIP, and EMSA. The biological effects of SP3 regulating BNIP3 on prostate cancer cells proliferation are measured by MTT, TUNEL, and flow cytometry. RESULTS Our data show that Sp3 but not Sp1, is positively related to BNIP3 overexpression in prostate cancer. Sp3 can directly regulate BNIP3 transcription by mainly binding to the Sp3 binding sites (−624∼−615 and −350∼−343) of BNIP3 promoter. Knockdown of Sp3 by RNA interference could reduce cells growth and lead to cells apoptosis in PC‐3 and DU145. Sp3‐dependent BNIP3 overexpression might be an important mechanism to promote prostate cancer cells proliferation. CONCLUSION This is the first study to provide direct evidence of Sp3‐dependent BNIP3 expression. Sp3 might be the major transcriptional regulator of BNIP3 in prostate cancer and it is worthy to further study. The regulation of BNIP3 by Sp3 may be a new cancer‐specific therapeutic target in prostate cancer. Prostate 75:1556–1567, 2015. © 2015 Wiley Periodicals, Inc.